6(3X+3)-2(9X+9)=

Simple and best practice solution for 6(3X+3)-2(9X+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3X+3)-2(9X+9)= equation:


Simplifying
6(3X + 3) + -2(9X + 9) = 0

Reorder the terms:
6(3 + 3X) + -2(9X + 9) = 0
(3 * 6 + 3X * 6) + -2(9X + 9) = 0
(18 + 18X) + -2(9X + 9) = 0

Reorder the terms:
18 + 18X + -2(9 + 9X) = 0
18 + 18X + (9 * -2 + 9X * -2) = 0
18 + 18X + (-18 + -18X) = 0

Reorder the terms:
18 + -18 + 18X + -18X = 0

Combine like terms: 18 + -18 = 0
0 + 18X + -18X = 0
18X + -18X = 0

Combine like terms: 18X + -18X = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 84=6(6-8n) | | 30=.5(12)(h) | | .5x+x= | | -2r-6r=8-7r | | 2-15y=5(-3y+2) | | 75C^2-192=0 | | 4x-2=-8+6x+x | | 3p+14=-24+5p | | 5.1q-3.5-4.69=0.5-2.4 | | 4(2-2X)-5(6-X)= | | 2x+-7=0.1(-7+3) | | -x^2+2x+.25=3 | | 3+7(x+8)=87 | | -x^2-2x+.25=3 | | .5x+x+1.25x= | | 11x=20x+8 | | 5(w+1)=3(w+1) | | 5(y+5)=21 | | 18.5+2.25h=47.75 | | 8(4v+4)=4(5+7V) | | 7-8b=10-b | | -3a+5a=-(4a+4)-(-a+1) | | -5h+3=-7 | | 5(y+7)=21 | | 4.65-4.79=13.57-6.84x | | -3a+5a=-(4a+4)-(-1+1) | | 92=86+a/2 | | 15=12+logx | | -4(8-x)+3=2+4(x+4) | | 4(-10)(-1)+9(-10)= | | t+86/2=92 | | (u-1)(u-3)=48 |

Equations solver categories